Landscape-scale variability of acidity and dissolved organic carbon during spring flood in a boreal stream network - Buffam, Ishi; Laudon, Hjalmar; Temnerud, Johan; Mörth, Carl-Magnus; Bishop, Kevin (Journal of Geophysical Research, 2007)
Acidity is well known to influence stream biota, but the less well‐studied spatial and temporal distributions of acidity are likely to play a larger ecological role than average values. We present data on spatial variability of chemical parameters contributing to acidity during winter baseflow and spring flood periods in Krycklan, a fourth‐order boreal stream network in northern Sweden. Fifteen stream sites were monitored in subcatchments spanning 3 orders of magnitude in size and representing a wide range of percent wetland. At baseflow, pH ranged from 3.9 to 6.5 at the different sites. Baseflow dissolved organic carbon (DOC) concentration varied by an order of magnitude and was positively correlated with subcatchment percent wetland, resulting in high spatial variability in dissociated organic acids (OA−). During spring flood, DOC and OA− increased in forested sites and decreased in wetland sites, resulting in reduced spatial variability in their concentrations. In contrast, base cations and strong acid anions diluted throughout the stream network, resulting in decreased acid neutralizing capacity (ANC) at all sites. The spatial variability of base cations increased slightly with high flow. As a result of the changes in OA− and ANC, pH dropped at all but the most acidic site, giving a slightly narrowed pH range during spring flood (4.2–6.1). The transition from winter to spring flood stream chemistry could largely be explained by: (1) a shift from mineral to upper riparian organic soil flow paths in forested catchments and (2) dilution of peat water with snowmelt in wetland catchments.